Major Histocompatibility Complex Variation and Haplotype Associated Survival in Response to Experimental Infection of Two Bd-GPL Strains Along a Latitudinal Gradient - Cortazar-Chinarro, Maria; Meurling, Sara; Schroyens, Laurens; Siljestam, Mattias; Richter-Boix, Alex; Laurila, Anssi; Höglund, Jacob (Frontiers in Ecology and Evolution, 2022)
While both innate and adaptive immune system mechanisms have been implicated in resistance against the chytrid fungus Batrachochytrium dendrobatitis (Bd), studies on the role of specific MHC haplotypes on Bd infection are rare. Here, we studied variation in MHC Class IIB loci in the common toad Bufo bufo along a latitudinal gradient across Sweden. In general, Swedish toad populations had few MHC Class IIB haplotypes and MHC diversity declined from south (13 haplotypes) to the north (four haplotypes). The low diversity may compromise the ability of northern populations to fight emerging disease, such as Bd. In a laboratory experiment, we infected newly metamorphosed toads with two strains of the Global Pandemic Lineage of the fungus (Bd-GPL) and compared survival with sham controls. Bd-infected toads had lower survival compared to controls. Moreover, survival was dependent on the Bd-strain and northern toads had lower Bd-mediated survival than southern individuals. MHC diversity was lower in northern toads. All northern experimental animals were monomorphic for a single MHC haplotype, whereas we found seven different haplotypes in southern experimental animals. In southern toads, survival was dependent on both Bd-strain and MHC haplotype suggesting differential infection dynamics depending on both Bd-strain and host immune system characteristics.